Peroxisome Proliferator-Activated Receptor-γ Promotes Adipogenic Changes in Growth Plate Chondrocytes In Vitro - Lai Wang; Yvonne Y. Shao; R. Tracy Ballock (PPAR Research)
Chondrocytes and adipocytes are two differentiated cell types which are both derived from mesenchymal cells. The purpose of this study was to investigate whether peroxisome proliferator-activated receptor-γ (PPARγ), a transcription factor involved in lineage determination during adipogenesis, is able to induce adipogenic differentiation in growth plate chondrocytes. Isolated epiphyseal chondrocytes were infected with a PPARγ adenovirus or treated with the PPARγ agonist ciglitazone. Both of these treatments resulted in lipid droplet accumulation and expression of the adipogenic markers aP2, lipoprotein lipase, and adipsin in chondrocytes. Proteoglycan matrix synthesis was decreased in the PPARγ-infected cells, as was the expression of the chondrogenic genes Col2a1 and aggrecan. Growth plate cells transfected with a PPARγ expression plasmid under the control of the collagen α1(II) promoter also demonstrated a similar adipogenic changes. Terminal differentiation of growth plate chondrocytes induced by thyroid hormone was also inhibited by overexpression of PPARγ and ciglitazone treatment, with decreased expression of alkaline phosphatase and Runx2/Cbfa1 genes. These in vitro data suggest that PPARγ is able to promote adipogenic differentiation in growth plate chondrocytes, while negatively regulating chondrogenic differentiation and terminal differentiation.